Pemberdayaan Kelompok Wanita Nelayan Desa Anaiwoi dan Totobo Melalui Pembuatan Surimi Beku - Permana, Dian; Asni, Asni; Erfna, Erfna; Marniati, Marniati; Mansyur, Mansyur (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
This dedication to the society aims to provide knowledge and training toward group of fishermen women in Totobo and Anawai village, Kolaka District, South East Sulawesi Province to processing their results of pond into frozen surimi. Implementation of community service is done by counseling about development of fish diversification in the form of surimi products and its derivative, then doing the practice of making frozen surimi. The results obtained are frozen surimi that from milkfish processing of fishery products of fishermen waomen group. In addition to other results of this devotion program in the form of capabilities obtained by the community in processing of milkfish meat to becoming frozen surimi, thereby expected to become a home industry